The Validity of Rector’s Circular Letter on the Covid-19 Pandemic - Fradhana Putra Disantara (UNIFIKASI : Jurnal Ilmu Hukum, 2020)
This study aims to analyze the relevance of the ‘health emergency’ status to the existing legal theory and condition as well as to identify the validity of the Circular Letter of the Rector of State Universities. To this end, this study applied the statute and conceptual approach. The study was conducted by inventorying primary and secondary legal materials to obtain a proper and critical review of the legal issues under study. The results showed that the determination of the ‘health emergency’ status by the government was inappropriate due to the uncertainty of the regulations issued by the government to determine the current condition. Thus, the status of the COVID-19 pandemic is a ‘legal emergency’ status. Further, the Rector’s policy through the Circular Letter is valid judicially, sociologically, and philosophically. The determination of the ‘legal emergency’ status can be done by issuing a Perppu without a ‘state of emergency’ from the President. Finally, it is suggested to firstly get an approval from the Ministry of Education and Culture regarding the issuance of the Rector’s Circular Letter. Besides, further study is needed as this study was conducted during the COVID-19 pandemic. Keabsahan Surat Edaran Rektor Perguruan Tinggi dalam Pandemi Covid-19Tujuan dari penelitian ini adalah untuk menganalisa relevansi status ‘darurat kesehatan’ dengan teori hukum dan kondisi yang ada dan keabsahan atas Surat Edaran Rektor Perguruan Tinggi Negeri. Metode yang digunakan dalam penelitian ini adalah statute approach dan conseptual approach. Penelitian dilakukan dengan menginventarisasi bahan hukum primer dan sekunder, guna mendapatkan kajian yang seyogianya dan telaah kritis terkait isu hukum. Hasil penelitian menyatakan penetapan status darurat kesehatan oleh pemerintah kurang tepat, dikarenakan tidak menentu-nya peraturan yang dikeluarkan oleh pemerintah untuk menetapkan kondisi saat ini. Sehingga, status pandemi COVID-19 merupakan status darurat hukum. Kebijakan rektor melalui Surat Edaran adalah absah secara aspek yuridis, sosiologis, dan filosofis. Penetapan darurat hukum cukup dilakukan dengan menerbitkan Perppu tanpa pernyataan darurat dari Presiden. Saran peneliti adalah di perlukan persetujuan pada Kementerian Pendidikan dan Kebudayaan terkait terbitnya Surat Edaran Rektor, dan dibutuhkan penelitian lebih lanjut dikarenakan penelitian ini dilakukan pada masa COVID-19 yang bersifat temporal.